2020
DOI: 10.1177/1120672120957599
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in CRX causing pigmented paravenous retinochoroidal atrophy

Abstract: Introduction: Mutations in the cone-rod homeobox ( CRX) gene, a known cause of inherited retinal dystrophy, are characterized by extensive phenotypic heterogeneity. We describe a novel presentation of rod-cone dystrophy (RCD) phenocopying pigmented paravenous retinochoroidal atrophy associated with a mutation in CRX. Case description: A 53-year-old man and his 48-year-old brother presented with a history of progressive vision loss and nyctalopia. Fundus examination revealed a bull’s eye lesion with chorioretin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 12 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…an early age[18]. Jin Kyun Oh et al reported a unique presentation of rod-cone dystrophy (RCD) resembling pigmented paravenous retinochoroidal atrophy, which was associated with a mutation in CRX[19]. In a recently reported case[20], Liu et al found that the pathogenic variants within the RPGRIP1 gene were implicated in the etiology of PPRCA.…”
mentioning
confidence: 99%
“…an early age[18]. Jin Kyun Oh et al reported a unique presentation of rod-cone dystrophy (RCD) resembling pigmented paravenous retinochoroidal atrophy, which was associated with a mutation in CRX[19]. In a recently reported case[20], Liu et al found that the pathogenic variants within the RPGRIP1 gene were implicated in the etiology of PPRCA.…”
mentioning
confidence: 99%
“…Retinochoroidal atrophy was reported in around 45% of studies (N = 27). Some reported varying degrees of severity, include "dense" and "severe" atrophy" [31,37]. It was also spread across different locations in the eyes, with some patients reporting atrophy "observed throughout" and others with more constricted presentations, such as "in the peripheral paravenous distribution" [26,37].…”
Section: Symptomsmentioning
confidence: 99%
“…At Patients 3's 6-month follow-up, "vision in the left eye had reduced to 'Counting Fingers'" [17]. For some no-treatment patients, there was a deterioration of symptoms including "progressive vision loss" and "progressive retinal thinning", "increased blind spots" and "deteriorated night vision" [17,24,31,44,[64][65][66]67] Patient 5 "exhibited no change at the 12-month follow-up" [42]. Patients 4 and 6 did not attend the followup [39,64].…”
Section: Genetic or Family Historymentioning
confidence: 99%
“…PPCRA has been reported to be most frequently sporadic, although some familiar cases have been reported, with many inheritance patterns being hypothesized. 3,[9][10][11][12][13][14][15][16]43,63 Noble et al reported the case of three siblings, all of whom had early (or maybe congenital) onset PPCRA, without a clear inheritance pattern. 9 Traversi and colleagues described a case of unilateral RP in a woman and PPCRA in her daughter and son.…”
Section: Familial Cases and Geneticsmentioning
confidence: 99%
“…1 To this date, mutations in only four genes have been associated with PPCRA. 12,25,63,64 McKay et al first reported the c.619G→A heterozygous mutation in the CRB1 gene in association with a family with PPCRA. 12 In particular, six out of the seven probands examined carried signs of the disease and the inheritance pattern was autosomal dominant.…”
Section: Familial Cases and Geneticsmentioning
confidence: 99%